Identification and Evaluation of Safety Hazards in Laboratories of the National Shrimp Research Institute and the Effectiveness of Measures by FMEA Technique - Maryam MIRBAKHSH; Ghafoor NOORIAN; Fariba ESMAEILI; Babak GHAEDNIA; Parisa HOSSEIN KHEZRI; Mohammad Ali NAZARI; Ehteram MOHAMMADI (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract: Introduction: Safety, raising awareness, and preventing the occurrence of hazards are necessary in order to continue to improve the quality of laboratory activities, which have been recently considered by scientific, research, and industrial communities. Therefore, the present study was conducted to determine the risk factor, potential hazards, and provide practical programs in the laboratories of the Shrimp Research Institute. Methods: Safety hazards of eight laboratories of the National Shrimp Research Institute were evaluated during the intervention study with the Failure Mode and Effects Analysis technique. To this end, in the first phase, the team of safety experts (HSE: Health and Safety Executive), by preparing and completing safety questionnaire forms, identified the current status of safety indicators and danger points of laboratories, assessed the distance with safety indicators, and managed danger points. Based on risk severity, probability of occurrence, and probability of risk detection, the risk priority number (RPN) was calculated, prioritized, and corrective measures were proposed. In the second phase, after corrective measures, the safety questionnaire was completed again and the level of risk severity, probability of occurrence, probability of detection, risk priority number, risk number, and percentage reduction of risk priority number of the studied laboratories were calculated and analyzed. Results: Thirty-five hazard points were identified in the laboratories. The range of risk priority numbers ranged from RPN = 12 for the Plankton Laboratory to RPN = 210 for the Marine Microbiology Laboratories and Marine Pollutants. After control measures, the risk number of marine microbiology laboratory was reduced to 180 and marine pollutants to 120 (P <0.05). Conclusion: The results showed that FMEA technique is appropriate in identifying the risk points, evaluating, and classifying the risks of the Iran Shrimp Research Institute laboratories and provide control strategies to eliminate or reduce the risk rate of research environments.